2018
DOI: 10.4103/0366-6999.226070
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Circular RNAs as a Novel Biomarker for Ovarian Endometriosis

Abstract: Background:Endometriosis is a challenging disease with symptoms such as dysmenorrhea and infertility. However, its etiology is still vague and there is still no effective markers or treatment. This study aimed to profile the circular RNAs (circRNAs) expressed in eutopic endometrium from patients with ovarian endometriosis and explore potential clues to the pathogenesis of endometriosis, providing an evidence for clinical diagnosis and treatment.Methods:A total of 63 clinical samples, including control endometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…In this study, we investigated circRNA expression profiles in ecEM compared with euEM of endometriosis patients and identified 294 differentially expressed circRNAs, 146 upregulated and 148 downregulated. Most of those dysregulated circRNAs originate from exons or introns which are in accordance with previous researches (Shen et al, ; Xu et al, , ; Zhang, Ren, Xiao, Xia, & Fang, ). It has been reported that both exonic and intronic circRNAs may exert potential functions in gene regulation (Greene et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we investigated circRNA expression profiles in ecEM compared with euEM of endometriosis patients and identified 294 differentially expressed circRNAs, 146 upregulated and 148 downregulated. Most of those dysregulated circRNAs originate from exons or introns which are in accordance with previous researches (Shen et al, ; Xu et al, , ; Zhang, Ren, Xiao, Xia, & Fang, ). It has been reported that both exonic and intronic circRNAs may exert potential functions in gene regulation (Greene et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…It has been reported that both exonic and intronic circRNAs may exert potential functions in gene regulation (Greene et al, ). Xu et al () revealed for the first time the circRNA expression patterns between women with and without endometriosis and found that the increased level of circ_0004712 and circ_0002198 could help identify the patients with endometriosis. Zhang, Ren, et al () assessed the expression profiles of circRNAs in endometriosis by microarray analysis and detected 2,237 circRNAs differentially expressed among ectopic endometrium (EC) (endometriotic lesions), paired eutopic endometrium (EU), and normal endometrium from women free of endometriosis, and qRT‐PCR validation suggested that downregulated circ_103470 and circ_101102 matched the microarray results.…”
Section: Discussionmentioning
confidence: 99%
“…[ 62 ] Another technique worth mentioning is miRNAs, which means small non-coding RNAs that repress translation thereby regulating the degree of gene expression. [ 44 ] Panir et al 's study [ 43 ] suggested that miRNA dysregulation may be involved in the pathophysiology of endometriosis and Xu et al [ 63 ] founded that circular RNAs are differentially expressed between eutopic and normal endometrium, but nowadays there is no non-coding RNA that can be used as reliable biomarkers for endometriosis no matter single or in panel. [ 44 ] However, with the continuous progress of experimental technologies, there will be more promising emerging technologies for us to try and explore in the future.…”
Section: Perspective and Conclusionmentioning
confidence: 99%
“…Unlike linear RNAs, circRNAs are protected against the effects of RNA enzymes due to their lack of free ends; these molecules are thus more stable compared with linear RNAs (5). With the development of RNA-seq analysis and bioinformatics technologies, recent studies have reported the use of circRNAs in the early detection and prognosis of certain types of cancer, such as gastric cancer (6), hepatocellular carcinoma (7), lung cancer (8), cervical squamous cell carcinoma (CSCC) and breast cancer (BRCA) (9), as well as a number of female reproductive system diseases including repeated implantation failure (10), preeclampsia (11) and ovarian endometriosis (12). Considering the association between hormone-responsive BRCA and the female reproductive system (13), this condition was included as a female reproductive system disease in the present meta-analysis.…”
Section: Introductionmentioning
confidence: 99%